Land Use Change Trend Assessment Using RS and Data GIS (Case Study: Urban Area of Ardabil) - Morteza Akbaryan; Diana Dortaj; Laila Abedi Fard (جغرافیا و پایداری محیط)
In recent years, population growth has led to the development of residential areas. The development of residential areas also causes changes in the type of land and size of the views. Considering the importance of land use change and its direct impact on human life, in this research, land use changes and land use development trend in the urban area of Ardabil has been studied. In this research Landsat satellite images were used to study land use changes. Preparing the images and performing the necessary preprocesses, the land use map of the study area for the years 1990, 2000 and 2010 was made in four classes of residential, agricultural, rangeland and water zones by using the maximum probability method. The results of the evaluations indicate that in the period from 1990 to 2010, residential lands have increased from 26.4 to 51.4 km2. However, with the increase of residential land and human infrastructure, agricultural use and rangelands reduced. Assessment of changes in residential areas indicates that most of the changes have taken place on the sidelines of the city of Ardabil. Due to the fact that rivers are often considered as attracting the population, over the recent years, the development of residential land has been towards the Balikhlochai River as well as the northern districts of Ardabil city.